Opportunities and barriers of local products’ sales in rural regions - Bótáné Horváth, Noémi (Acta Agraria Debreceniensis, 2014)
Nowadays local economy systems are highlighted in the Hungarian, the European and also in the global economy system. Inhabitants and local products, services created by them are the most important elements of local economy systems. Local products are especially important in areas with special conditions, in the underprivileged rural areas. Sales of these products and services on local level and above could give answer to economic and social challenges in these regions. In the same time to become part of the economic system selecting the best marketing channels for these products is very important. In this study, based on a case study in Mezőcsát, possible marketing channels are revealed through quantitative research based on primer and secunder data and SWOT analysis. In the case of Mezőcsát for local sales the best place is the local market, while webshop is the best for sales outside Mezőcsát.